(untitled) (Journal of the Bangladesh Agricultural University, 2025)
The short shelf life of jujube is a problem for postharvest preservation and the fruit industry. This study aimed to evaluate the effect of chitosan on postharvest quality, including the shelf life of jujube. The experiment consisted of four treatments (control, 0.1% chitosan, 0.3% chitosan, and 0.5% chitosan) and five jujube varieties (Ball Sundori Kul, Apple Kul, Kashmiri Kul, Thai Kul, and Narkeli Kul) and was laid out in a Completely Randomized Design with three replications. Data were collected on weight loss, fruit length, breadth, color attributes [L* (lightness), a* (redness or greenness), b* (blueness or yellowness), C* (chroma), and h° (hue angle)], total soluble solids, titratable acidity, vitamin C, pH, flavonoids, anthocyanins, and disease incidence, generally at 3, 6, and 9 days after storage (DAS). Fruits were also evaluated for shelf life. The minimum weight loss (14.33%) was recorded from 0.5% chitosan-coated Ball Sundori Kul. The 5% chitosan also resulted in better colorimeter values (*L, a*, b*, C*, and h*) than the other treatments. Ball Sundori Kul coated with 0.5% chitosan showed the highest Vit C (19.62 mg100g-1) and TSS (15.13%), while uncoated fruit had the highest pH (4.11) at 9 DAS. Moreover, Ball Sundori Kul coated with 0.5% chitosan retained the highest total flavonoid (0.90 mg100g-1) and total anthocyanin (35.25 mg100g-1), and the lowest disease incidence (55%). Furthermore, Ball Sundori Kul coated with 0.5% chitosan had the highest shelf life (9 days). Therefore, jujube fruits, particularly Ball Sundori Kul, can be coated with 0.5% chitosan for postharvest preservation. J Bangladesh Agril Univ 23(3): 398–409, 2025